Evaluación del extracto etanólico de mosquera “croton elegans”, en concentracion de 10, 20 y 30% a dosis de 2ml; en cicatrizacion post- quirurgica en ovario histerectomia en caninas mestizas en el centro de gestion zonal animal de carapungo en el Distrito Metropolitano - Barrionuevo Mayorga, Alejandra Elizabeth (2011)
In the chapter I of the thesis we found theory mark, in first place an introduction that allow us have a clear idea about the realized investigation, the medical use of ethnics plants in our country specially the Croton elegans (Mosquera) use, his description, phytoquimics properties, the against activity with the organism aggressors and all over cicatrizing action mechanism . It gives little description of anatomy of the female dog reproduce organs, also it details the surgery techniques to Ovarian Hysterectomy in female dogs, and then it describe the cicatrizing, cicatrizing physiology that I consider a useful bibliographic contribution, cause this thesis is orientated to value the post- surgery cicatrizing process to applythe phytopharmacology to proof the Mosquera action....